Integrated analysis of Xist upregulation and X-chromosome inactivation with single-cell and single-allele resolution - Guido Pacini (Nature Portfolio, 2021)
X-chromosome inactivation (XCI) ensures dosage compensation between the sexes. Here the authors perform allele-specific single-cell RNA sequencing in differentiating mouse embryonic stem cells to provide a detailed profile of the onset of XCI.